2002
DOI: 10.1021/pr025552q
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Constraints for Protein Structure Prediction

Abstract: Though highly desirable, neither a single experimental technique nor a computational approach can be sufficient enough to rationalize a protein structure. The incorporation of biophysical constraints, which can be rationalized based on conventional biophysical measurements, might lead to considerable improvement of the simulation procedures. In this regard, our analysis of 180 proteins in different conformational states allows prediction of the overall protein dimension based on the chain length, i.e., the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 22 publications
(40 reference statements)
9
60
0
1
Order By: Relevance
“…S1), subjected each to size fractionation in sieving columns to measure their R S (Table I), and compared the measured R S values with the predicted R S values for proteins of equal mass in various hypothetical structural configurations such as folded, molten globule, premolten globule, relaxed coil, extended coil (as in urea), or very extended coil (as in guanidinium hydrochloride). The latter values were obtained using the scaling relations reported (40). The sieving experiments were conducted at 30°C, which is a physiologically relevant temperature for yeast growth.…”
Section: Distinct Categories Of Intrinsically Disordered Structures Imentioning
confidence: 99%
See 2 more Smart Citations
“…S1), subjected each to size fractionation in sieving columns to measure their R S (Table I), and compared the measured R S values with the predicted R S values for proteins of equal mass in various hypothetical structural configurations such as folded, molten globule, premolten globule, relaxed coil, extended coil (as in urea), or very extended coil (as in guanidinium hydrochloride). The latter values were obtained using the scaling relations reported (40). The sieving experiments were conducted at 30°C, which is a physiologically relevant temperature for yeast growth.…”
Section: Distinct Categories Of Intrinsically Disordered Structures Imentioning
confidence: 99%
“…Finally, we used scaling equations (40) to calculate the hydrodynamic volume of all yeast FG domains and stalk regions, adjusting for the mass of the entire domain when necessary (in cases where only a fragment was analyzed here; compare Tables I and II). The derived R h /R S values were then used to estimate (i) the molecular diameter of each FG domain or stalk assuming it is a sphere, (ii) the hydrodynamic volume it would occupy in isolation, and (iii) the combined volume that all intrinsically disordered nup domains would occupy at the NPC given their stoichiometry there (52).…”
Section: Fig 5 Test Of Low Affinity Interaction Between Fg Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis gave rise to a set of the standard equations for a polypeptide chain in a number of conformational states (46) where N, MG, PMG, U(urea), and U(GdmCl) correspond to the native, molten globule, premolten globule, urea -, and GdmCl -unfolded globular proteins, respectively, whereas NU(coil) and NU(PMG) correspond to native coil -like and native premolten globule -like proteins, respectively. Importantly, statistical analysis has revealed that the relative errors of the recovered approximations exhibit random distribution over the wide range of chain lengths and do not generally exceed 10% (37) . This means that the effective protein dimensions in a variety of conformational states can be predicted based on the chain length with an accuracy of 10%.…”
Section: Evaluating Hydrodynamic Dimensions Of Proteins In Different mentioning
confidence: 99%
“…Transformation of a typical globular protein into a molten globule state results in a ∼ 15 -20% increase in its hydrodynamic radius (32,33,39,41,44,45) . The relative increase in hydrodynamic volume of less folded intermediates is even larger (33,37,39,44,54,55) . Figure 18.2 shows that the folded and unfolded conformations of globular proteins possess very different molecular mass dependencies of their hydrodynamic radii, R S (37 -39, 43, 44) .…”
Section: Knowing Idp Conformation From Sec Measurementsmentioning
confidence: 99%